The effects of exercise on oxidative stress MDA and SOD in patients with type 2 diabetes: a systematic review and meta-analysis - Chen Qiu; Shufan Li; Shuqi Jia; Fen Yu; Chen Wei; Xing Wang; Bo Guo (PeerJ)
Objective Systematic review of the effect of exercise intervention on oxidative stress in patients with type 2 diabetes mellitus (T2DM). Methods Databases such as Embase, Web of Science, PubMed, The Cochrane Library, Wanfang, VIP, and China National Knowledge Infrastructure were searched from their inception to June 2024. PEDro was used to assess the quality of the literature, RevMan 5.4.1 and Stata 17.0 were used to perform meta-analysis and publication bias tests, respectively, and GRADEPro was used to evaluate the quality of the evidence for outcome indicators. Standardized mean difference (SMD) and 95% confidence interval (CI) were used as effect measures. Results This study included 11 articles (1,111 patients). The results of the meta-analysis showed that exercise can improve malondialdehyde (MDA), standardized mean difference (SMD) = −1.29, 95% CI [−1.87 to −0.71], P < 0.0001 in patients with T2DM; and improve superoxide dismutase (SOD), SMD = 0.59, 95% CI [0.17–1.01], P = 0.006 in patients with T2DM. Subgroup analysis showed that exercise can improve MDA and SOD in patients aged >60 years. The effect is significant when the intervention method is aerobic exercise and combined exercise. The intervention period should be >12 weeks and intervention frequency <3 days/week. Exercise is more effective in improving MDA, an indicator of oxidative stress, when the intervention method is aerobic exercise, the period is >12 weeks and the frequency is <5 days/week, which improves oxidative stress indicators SOD. Discussion This study included 11 articles with an average PEDro score of 6.5, indicating good quality. Subgroup and sensitivity analyses of the oxidative stress indicators MDA and SOD failed to identify sources of heterogeneity, which is a limitation. Publication bias tests for the oxidative stress indicators MDA and SOD suggest that there is no significant publication bias. Therefore, moderate-quality evidence is given to the oxidative stress indicator MDA, and high-quality evidence is given to the oxidative stress indicator SOD. Exercise has a significant effect on improving oxidative stress indicators MDA and SOD in patients with type 2 diabetes. It is affected by the patient’s age, the method, duration, and frequency of the intervention. It can provide evidence-based medical evidence for the clinical rehabilitation of patients with type 2 diabetes.